Pengaruh Hubungan Ketebalan dan Effective Size Media Filter Terhadap Efektifitas Filtrasi Saringan Pasir Cepat - Didin Solahudin (DPPM Universitas Pelita Bangsa, 2024)
Rapid sand filter is the most common type of filter used by water treatment plants. Some installations have difficulty to determining the right effective size of media and media thickness to obtain the expected quality and quantity of treated water. Considering the lack of practical guidance available for Water Treatment Plant (WTP) managements to determine the thickness and effective size of filter media, observations were made of several variations in the thickness and effective size of filter media in operating plants. This research was conducted to compare the filtration effectiveness of several variations in thickness and effective size of filter media, so that WTP managers can prepare filter maintenance and operation planning effectively and efficiently. The research method was carried out by observing filters that had variations in the thickness and effective size of the silica sand media. Filtration effectiveness is measured by comparing the turbidity of the inlet and outlet filters of each filter. Data evaluation was carried out using trend analysis and correlation analysis approaches. Media thickness giving effect to the filtration effectiveness at an effective size of 1.01-1.02 mm with a correlation R2: 0.9359. The thickness of filter media also giving effect to the standard deviation on filtration effectiveness, this can be seen from the correlation R2: 0.9616. In a filter unit with filtration rate around 12.9-13.7 m/hour, the use of filter media with an effective size of 1.01-1.02 mm and 1.0 - 1.2 m thickness can provide filtration effectiveness around 83.8% - 87.3%.